2002
DOI: 10.1099/0022-1317-83-11-2897
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of prion diseases by blood transfusion

Abstract: Attempts to detect infectivity in the blood of humans and animals affected with transmissible spongiform encephalopathies (TSEs or prion diseases) have often been inconclusive because of the limitations of cross-species bioassays and the small volumes of blood that can be injected by the intracerebral route. A model has been developed for the experimental study of TSE transmission by blood transfusion using sheep experimentally infected with bovine spongiform encephalopathy (BSE) or natural scrapie as donors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
318
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(336 citation statements)
references
References 30 publications
11
318
1
4
Order By: Relevance
“…Prions are present in the blood of infected animals, since the disease has been shown to be transmitted by transfusionÅ [12].Å HoweverÅ becauseÅ ofÅ theÅ highÅ specificÅ infectivity of purified prion preparations (as high as 10 11 infectious units (IU) per milligram of protein purified fromÅ SyrianÅ hamstersÅ inoculatedÅ withÅ strainÅ 263K)Å [13], and the fact that in rodent models of TSE, blood contains 5 to 10 IU/mL in preclinical animals and a maximum of about 100 IU/mL at the time of disease onset, it has been estimated that blood contains about 0.05Å toÅ 1.0Å pgÅ (30Å -Å 625Å amol)Å ofÅ PrP ScÅ perÅ mLÅ [14].…”
mentioning
confidence: 99%
“…Prions are present in the blood of infected animals, since the disease has been shown to be transmitted by transfusionÅ [12].Å HoweverÅ becauseÅ ofÅ theÅ highÅ specificÅ infectivity of purified prion preparations (as high as 10 11 infectious units (IU) per milligram of protein purified fromÅ SyrianÅ hamstersÅ inoculatedÅ withÅ strainÅ 263K)Å [13], and the fact that in rodent models of TSE, blood contains 5 to 10 IU/mL in preclinical animals and a maximum of about 100 IU/mL at the time of disease onset, it has been estimated that blood contains about 0.05Å toÅ 1.0Å pgÅ (30Å -Å 625Å amol)Å ofÅ PrP ScÅ perÅ mLÅ [14].…”
mentioning
confidence: 99%
“…Studies in ruminants have analysed bioassays of autologous whole or fractionated blood by the intravenous route [19,20]. These experimental transfusion studies have confirmed that all blood fractions prepared by protocols similar to those used in transfusion medicine can transmit prion disease [23,24]. In addition, prion transmission by transfusion of cellular blood fractions was not solely dependent on their infectious titre since prion disease was more efficiently transmitted with viable rather than non-viable leukocytes [20].…”
Section: Introductionmentioning
confidence: 92%
“…[46] is of particular relevance since the tissue distribution of both infectivity and PrP Sc in sheep with BSE and scrapie closely resembles that in vCJD in humans. Furthermore, the route of infection in this experimental model (oral challenge with BSE-infected brain tissue) is in keeping with the postulated (but not proven) route of BSE infection in vCJD.…”
Section: Evidence For Infectivity In Blood In Prion Diseasesmentioning
confidence: 97%
“…A preliminary result of positive transmission of BSE by blood transfusion from a sheep in the preclinical stage of the disease [43] attracted some criticism in view of the lack of control data [44,45]. However, a recent updated publication has reported that an additional BSE transmission by transfusion of whole blood from a donor animal during the preclinical stage of infection has occurred, with two further animals showing early signs of BSE, having been transfused with whole blood taken when the donors were themselves in the clinical phase of BSE [46]. Assuming that the two recent suspect cases are confirmed, the minimum rate of BSE infection by transfusion in this series is approximately 17%.…”
Section: Evidence For Infectivity In Blood In Prion Diseasesmentioning
confidence: 99%
See 1 more Smart Citation